Improving Students’ Reading Comprehension through the Use of Pre-Reading Tasks at the Eight Grade of SMP Negeri 1 Mepanga - Rahmi Mawadah; Mukrim Mukrim; Agussatriana Agussatriana; Andi Patmasari (Journal of English Language and Education, 2026)
Reading comprehension is a key component of English as a Foreign Language (EFL) learning, as it supports vocabulary development, critical thinking, and academic achievement. Although theory highlights the importance of activating students’ prior knowledge before reading, classroom instruction often begins directly with the text, creating a gap between pedagogical principles and actual practice. This mismatch may contribute to students’ limited understanding and low engagement in reading activities. This study aimed to determine the effect of pre-reading tasks on the reading comprehension of eighth-grade students at SMP Negeri 1 Mepanga. A quasi-experimental design was employed, involving 49 students, with 25 students in the experimental group and 24 students in the control group. The experimental group was taught using specific pre-reading activities, including brainstorming, skimming, and vocabulary preview, while the control group received conventional instruction. Data were collected through pre-test and post-test instruments and analyzed statistically. The findings revealed that students exposed to pre-reading tasks achieved significantly better results than those in the control group. It can be concluded that pre-reading activities effectively enhance students’ reading comprehension.